Exome sequencing identifies variants in infants with sacral agenesis. Issue 7 (10th March 2022) - Pitsava, Georgia; Feldkamp, Marcia L.; Pankratz, Nathan; Lane, John; Kay, Denise M.; Conway, Kristin M.; Hobbs, Charlotte; Shaw, Gary M.; Reefhuis, Jennita; Jenkins, Mary M.; Almli, Lynn M.; Moore, Cynthia; et al.
Abstract: Background: Sacral agenesis (SA) consists of partial or complete absence of the caudal end of the spine and often presents with additional birth defects. Several studies have examined gene variants for syndromic forms of SA, but only one has examined exomes of children with non‐syndromic SA. Methods: Using buccal cell specimens from families of children with non‐syndromic SA, exomes of 28 child–parent trios (eight with and 20 without a maternal diagnosis of pregestational diabetes) and two child–father duos (neither with diagnosis of maternal pregestational diabetes) were exome sequenced. Results: Three children had heterozygous missense variants in ID1 (Inhibitor of DNA Binding 1), with CADD scores >20 (top 1% of deleterious variants in the genome); two children inherited the variant from their fathers and one from the child's mother. Rare missense variants were also detected in PDZD2 (PDZ Domain Containing 2; N  = 1) and SPTBN5 (Spectrin Beta, Non‐erythrocytic 5; N  = 2), two genes previously suggested to be associated with SA etiology. Examination of variants with autosomal recessive and X‐linked recessive inheritance identified five and two missense variants, respectively. Compound heterozygous variants were identified in several genes. In addition, 12 de novo variants were identified, all in different genes in different children. Conclusions: To our knowledge, this is the first study reporting a possible association between ID1 and non‐syndromic SA. Although maternal pregestational diabetes has been strongly associated with SA, the missense variants in ID1 identified in two of three children were paternally inherited. These findings add to the knowledge of gene variants associated with non‐syndromic SA and provide data for future studies.